1986
DOI: 10.1021/ja00283a051
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethyleneethane, a ground-state triplet

Abstract: enantiomeric selectivity occurs as well with cleavage. With A-R u ( T M P )~~+ , twice the cleavage efficiency of the A-form polymer is observed in comparison with A-Ru(TMP)~*+.In summary, A-Ru(TMP);+ has been shown to bind selectively to A-form polynucleotides and in the presence of light to cleave A-form polymers. This chiral probe should be useful to investigate DNA conformational heterogeneity in mapping sites in the A conformation along the helical strand. The role played by DNA secondary structures in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 0 publications
0
53
1
Order By: Relevance
“…These results, however, conflict with the ESR experiment, 128 which indicates a D 2d triplet conformation. Both the lowest energy singlet and triplet have D 2 symmetry; the angle is 58.0 ∘ for the singlet and 59.0 ∘ for the triplet.…”
contrasting
confidence: 73%
See 1 more Smart Citation
“…These results, however, conflict with the ESR experiment, 128 which indicates a D 2d triplet conformation. Both the lowest energy singlet and triplet have D 2 symmetry; the angle is 58.0 ∘ for the singlet and 59.0 ∘ for the triplet.…”
contrasting
confidence: 73%
“…Dowd,128 in 1986, prepared TME by photolysis of 4,5-bis(methylene)-3,4,5,6-tetrahydropyridazine 35 in a methyltetrahydrofuran glass at 10 K. The ESR spectrum The following year, Borden 129 reported computations of TME at three geometries: D 2h , D 2d , and D 2 . Dowd,128 in 1986, prepared TME by photolysis of 4,5-bis(methylene)-3,4,5,6-tetrahydropyridazine 35 in a methyltetrahydrofuran glass at 10 K. The ESR spectrum The following year, Borden 129 reported computations of TME at three geometries: D 2h , D 2d , and D 2 .…”
Section: Is Tme a Ground-state Singlet Or Triplet?mentioning
confidence: 99%
“…(B) Description of various structural forms of TME emerging from the torsion of the central carbon-carbon bond nearly degenerate (obey the Ovchinnikov's rule) that are responsible for the diradical character and hence obtaining a definite order of the singlet and triplet states of TME is not easy task. [102][103][104][105][106][107][108][109][110][111][112][113] Despite various works on TME, determination of the shape of twisting potential for the lowest energy singlet and triplet states is a challenging task as the system easily twists around the central C C bond and various methods encountered give an unbalanced account of the intricate interplay of different correlation effects in the two low-lying electronic states. Note that the singlet and triplet energy surfaces could cross one another as the twisting angle is varied.…”
Section: Tetramethyleneethanementioning
confidence: 99%
“…[9] However, using gas-phase negative ion photoelectron spectroscopy, Clifford et al [8] found that the singlet state of TME is about 2 kcal mol À1 below the triplet state. Experimental data reported by Iwamura, [10] based on EPR and superconducting quantum interference device measurements, unambiguously evidenced that the ground state for TME is singlet which is nearly degenerate (within a few cal mol À1 ) with 3 [TME].…”
Section: Introductionmentioning
confidence: 99%